Towards biologically active heterocycles from renewable aromatic starting materials - Anderson, Edward (2019)
This thesis describes work undertaken over the past three years as part of the EPSRC Centre for Doctoral Training in Sustainable Chemistry. Our focus was on developing methods to generate the same important molecules in new, and better ways as judged by green & sustainability criteria. Overall, we have concentrated our efforts on the synthesis of heterocyclic molecules within the context of biologically active molecules. This has ranged from the synthesis of aromatic heterocycles in the form of naphthyridines, to the dearomatisation of aromatic molecules to generate spirocyclic, unsaturated amines. We have successfully developed a greener, as judged by reaction metrics, method for the synthesis of 1,8-naphthyridines. In addition, we have produced a method for the synthesis of a previously unreported heterocycle that can likely find use as an electrophilic building block in synthetic chemistry. Furthermore, we have shown that one can oxidatively dearomatise phenols in the presence of tethered tertiary tert-butyl carbamates to afford spirocyclic tertiary amine products, using iodine(III) reagents as an oxidant.